Answer:
(5 x + 1) - (-10 x + 6)
5x +1 + 10x - 6
25x - 5
Step-by-step explanation:
(x - 2) - (6x - 9)
x - 2 - 6x + 9 =
-5x +7
(5 x + 1) - (-10 x + 6)
5x +1 + 10x - 6
25x - 5
-4 x + 2 x + 7 - 3 x
-5x + 7
(4 x + 3) + (-9 x + 4)
4x +3 -9x + 4
-5x + 7
Y-int, x=0
y = 2(0) therefore y-int is (0,0)
x-int, y=0
0=2x
x = 0 therefore x-int is (0,0)
5
Mark brainliest please
Hope this helps you
Answer:
L= 11
Step-by-step explanation:
Formula to find the length when you know the area:
L = A/W
So the equation for this one is:
L = 93 1/2 ÷ 8 1/2
Simplify:
L = 11
To be sure of your answer you multiply the L x W = A
11 x 8 1/2 = 93 1/2
Hope this helped : D